Interação entre grau de perda auditiva e o incômodo com zumbidos em trabalhadores com história de exposição ao ruído - Dias, Adriano [UNESP]; Cordeiro, Ricardo [UNESP] (FapUNIFESP (SciELO), 2008)
Hearing loss and tinnitus impact the lives of workers in every instance of their lives. Aim: this paper aims to investigate the existence of a dose-response relationship between hearing loss and tinnitus by determining whether higher levels of hearing loss can be associated with increased tinnitus-related discomfort. Materials and method: this cross-sectional case study assessed 284 workers exposed to occupational noise through pure tone audiometry. Test results were categorized as defined by Merluzzi. Individuals complaining of tinnitus answered the adapted and validated Brazilian Portuguese version of the Tinnitus Handicap Inventory. A generalized linear model was adjusted for binomial data to test the interaction between these factors. Results: over 60% of the ears analyzed had hearing loss, while more than 46% of them had tinnitus. Tinnitus prevalence and risk rates increased as pure tone audiometry results got worse. The association between both, considering all hearing loss degrees, was statistically significant. Conclusion: the results point to a statistical association between hearing loss and tinnitus; the greater the hearing loss, the greater the discomfort introduced by tinnitus. 2009 © Revista Brasileira de Otorrinolaringologia.
Association between hearing loss level and degree of discomfort introduced by tinnitus in workers exposed to noise
Keywords: Noise-induced hearing loss; Occupational noise; Tinnitus; adult; aged; auditory threshold; controlled study; disease association; disease classification; disease severity; female; hearing loss; human; industrial noise; major clinical study; male; occupational exposure; prevalence; pure tone audiometry; risk assessment; structured questionnaire; tinnitus; Adult; Aged; Audiometry, Pure-Tone; Brazil; Cross-Sectional Studies; Female; Hearing Loss, Noise-Induced; Humans; Male; Middle Aged; Noise, Occupational; Occupational Diseases; Prevalence; Questionnaires; Severity of Illness Index